The Effect of Methylphenidate on The Consciousness Level of Intoxicated Patients; a Double-Blind Clinical Trial - Zandiyeh, Faraz; Ramezani, Maral; Abiyarghamsari, Mahdieh; Shadnia, Shahin; Mostafazadeh, Babak; Erfan Talab Evini, Peyman; Mehrpour, Omid; Rahimi, Mitra (Archives of Academic Emergency Medicine, 2025)
Introduction: Intoxication-related unconsciousness is a frequent and challenging condition in emergency medicine, where rapid interventions are critical to improve patient outcomes. This study aimed to evaluate the efficacy of methylphenidate in improving consciousness levels of intoxicated patients. Methods: In this double-blind clinical trial, intoxicated patients over 18 years of age with the Glasgow Coma Score (GCS) 13 and below were studied. 51 people were included in the intervention group and received methylphenidate, while 50 were in the control group and received placebo. Consciousness levels were measured using the Reed score before and at 12, 24, 36, and 48 hours post-intervention and compared between groups using SPSS software version 21. Results: 101 patients with the mean age of 34± 14.26 (range: 17-81) years were studied (55.4% male). 74.5% of the people in the intervention group achieved the most alert state (a REED score of zero) after 48 hours, compared to only 32% in the control group. The intervention group had significantly lower average Reed scale (0.33) compared to the control group (0.76) 48 hours after the treatment (p = 0.001). Using Methylphenidate in treatment of intoxicated patients showed effect size of 0.703 (95% confidence interval (CI): 0.299-1.104), number needed to treat of 2.17 (95%CI: 1.48 - 3.34), absolute risk reduction of 46% (95%CI: 0.29 -0.67), and relative risk reduction of 57% (95%CI: 0.37 - 0.72). Conclusion: It seems that, the use of methylphenidate in patients with intoxication can reduce the time it takes for their consciousness to return to a normal level. Since benzodiazepines are the leading cause of poisoning, this study suggests that methylphenidate could be beneficial in cases of benzodiazepine poisoning to aid in cognitive recovery.